Varieties of capitalists? The middle class, private sector and economic outcomes in Africa - Antoinette Handley (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
Political scientists have generally seen two key features of African political economies - a relatively small or absent middle class, and a middle class that is unusually embedded in the state - as key explanations of the troubled political and economic trajectories of many African societies. This paper considers the nature and implications of recent momentous changes for Africa's political economies. It asks if there is such a thing as a homogenous and universal middle class, what its attributes and role are, and how these connect to the trajectory of the broader political economy.
Keywords: P16; P50; 330; Africa; middle class; private sector